Research Output on the Yazidi Minority After the ISIS Terrorist Attack: A Bibliometric Analysis - Arazoo Rasool Ahmed; Manvender Kaur A/P Sarjit Singh (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
This paper aims to conduct a bibliometric analysis of scholarly literature on the Yazidi community published between 2014 and 2021. The data for this study were retrieved from "Scopus" using relevant search terms in titles, abstracts, and authors’ keywords. The analysis of the literature is based on different parameters, allowing for a comprehensive mapping of the existing literature on the Yazidi community. The results indicate that the number of studies conducted on the Yazidi community is inadequate given the gravity of the situation. Furthermore, there is a significant discrepancy between the number of funded studies and unfunded studies. The majority of the extracted papers reviewed were affiliated with universities and other institutions of higher education. Through co-word analysis via Vos Viewer, this study identifies four clusters within literature. The findings of this study have significant implications for governmental and institutional agencies, as well as academics, in furthering their understanding and response to the Yazidi crisis. This paper provides valuable insights into recent research trends, emerging opportunities, and current topics in Yazidi studies for academics. Finally, this study highlights the broader social and long-term implications of the Yazidi crisis, underscoring the importance of continued research and policymaking on this issue.